PENINGKATAN NILAI JUAL PRODUK UMKM MELALUI PELATIHAN PEMBUATAN KERUPUK DARI TELUR ASIN DESA SIREMEN, KECAMATAN TANARA KABUPATEN SERANG - Azizurrohim Azizurrohim; Dinar Okto Praditya; Rani Puspa; Mega Selfina; Voni Dwi Juliana; Vina Sefia Febriyanti; Ayu Asari (Yayasan Education and Social Center, 2023)
The implementation of community service duties is an obligation required by lecturers together with students. This activity was carried out in Siremen Village, Tanara District. The purpose of this service is to improve the skills and standard of living of the community by producing innovative products from MSMEs. It is expected that innovations in such products will increase their attractiveness and thus, generate greater profits for the business actors. At present, salted eggs sold are generally just marinated duck eggs, so new creations are needed to develop them. The process of making crackers from salted eggs does not require a large investment, but ingenuity and creative ability are needed to increase the value of the product. By conducting training on making crackers from salted eggs, the goal is to hone the creative skills of business actors while increasing their income. In this training, packaging and labeling methods are also taught so that products become more attractive and clean. In addition, the hope is that this salted egg cracker product will access a wider market segment, so that it can become a favorite among the public. Community service activities, in addition to challenging lecturers and students to be more creative and innovative, will also improve the quality and continuity of products in the future